Development of a Digital Standing Samsak as a Tool for Testing Kicking Ability in Jambi City Pencak Silat Athletes - yonifia anjanika; Fitri Diana; sukendro; sugih suhartini; Yusra Dinafi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Currently, almost all training activities in the pencak silat sport use various technologies that are currently trending. However, there are several manual tools that are still used in practicing pencak silat techniques, namely punching pads which are used to practice various kicks and punches so that they become strong and fast. This punching pad is usually also used as a tool to test kicking and punching abilities. The problem that often occurs is that the accuracy of timing when kicking becomes out of sync, one of which is still using a stopwatch which often results in human error, this is of course very detrimental to athletes who don't know how far their abilities in kicking have progressed. This research aims to to develop a manual standing samsak tool made into a digital standing samsak that can be used to test kicking ability. The method in this research is to use the ADDIE development method. From the results of this research, it was found that this development product was worthy of being a tool for conducting pencak silat kick tests with a score obtained through two stages of validation by media experts and material experts and trials, namely, 86% of the score from media experts, 95.38%. % from material experts and 83.71% of the value from field trials, with this, the average value obtained from the three stages above is 88.36%. Thus it can be said that the product "Development of Standing Samsak Digital" is categorized as eligible with the criteria "GOOD"